Healthy dietary patterns and ovarian cancer risk and survival: a systematic review and meta-analysis - Xu, Yiyi; Chen, Jiner; Zhao, Ke (Frontiers in Nutrition, 2025)
BackgroundStudies investigating the associations between healthy dietary pattern and risk and survival of ovarian cancer have been limited and inconsistent. Therefore, we carried out this comprehensive systematic review and meta-analysis to analyze the available literature on the associations between healthy dietary patterns and risk and survival of ovarian cancer.MethodsPubMed, Web of Science, Scopus and China National Knowledge Infrastructure (CNKI) were comprehensively searched for the relevant articles published from databases inception to October 2024. According to heterogeneity, the pooled relative risks (RRs) and 95% confidence intervals (CIs) were calculated for the highest versus the lowest categories of healthy dietary patterns in relation to ovarian cancer risk and survival, using the random-effects or fixed-effects meta-analyses.ResultsSixteen studies (12 cohort and four case-control studies) with 615,203 participants, 5,452 ovarian cancer cases and 3,028 ovarian cancer deaths were included in the final analysis. Combining 15 effect sizes from eight studies, we found the evidence of a reduced risk of ovarian cancer in the highest compared with the lowest categories of healthy dietary patterns (RR = 0.91; 95%CI: 0.85–0.98, P = 0.013). The pooled analyses also revealed that healthy dietary patterns was associated with improved ovarian cancer survival (RR = 0.85; 95% CI:0.0.76–0.95, P = 0.004), with significant heterogeneity (I2 = 54.3%, P = 0.004). Moreover, per SD increment in healthy dietary score was related to a 14% reduced risk of ovarian cancer mortality (RR = 0.86; 95% CI: 0.81–0.91, P < 0.001).ConclusionOur findings demonstrated that high adherence to the healthy dietary patterns was associated with a reduced risk and improved survival of ovarian cancer. Future large-scale prospective studies are required to confirm and strengthen these findings.